TRACKING CHANGES IN THE UPPER BOUNDARY OF THE HEAVY-INTENSITY EXERCISE DOMAIN: END-TEST POWER VERSUS RESPIRATORY COMPENSATION POINT (Kinesiology, 2017)
The aim of this study was to compare how respiratory compensation point (RCP) and end-test power (EP) change in response to the same four-week high intensity interval training (HIIT). The power output associated with RCP and EP before and after HIIT were recorded in 24 recreationally active participants (14 men and 10 women). RCP was determined from an incremental exercise test and EP was derived from a three-minute maximal effort test on a cycle ergometer. A significant time (pretest/posttest) × measurement (EP/RCP) interaction was found (F(1, 23)=5.119, p